2017
DOI: 10.1016/j.bandl.2016.05.003
|View full text |Cite
|
Sign up to set email alerts
|

Hemispheric processing of memory is affected by sleep

Abstract: Sleep is known to affect learning and memory, but the extent to which it influences behavioural processing in the left and right hemispheres of the brain is as yet unknown. We tested two hypotheses about lateralised effects of sleep on recognition memory for words: whether sleep reactivated recent experiences of words promoting access to the long-term store in the left hemisphere (LH), and whether sleep enhanced spreading activation differentially in semantic networks in the hemispheres. In Experiment 1, parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
0
2

Year Published

2017
2017
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(22 citation statements)
references
References 70 publications
2
18
0
2
Order By: Relevance
“…Lateralising stimuli to the RH may highlight false memory effects, but naps rather than overnight sleep may also increase false memory effects (Chatburn et al, 2014). Indeed, the results of our study, and that of previous studies of lateralisation of DRM stimuli (Bellamy & Shillcock, 2007;Ito, 2001;Monaghan et al, 2017;Westerberg & Marsolek, 2003) are consistent with the possibility that false memories may be generated in the RH. Dominance of false memory generation in the RH would be consistent with the two principal theories for sleep-induced processing changes associated with false memories -the gist theory (Brainerd & Reyna, 2005;Durrant & Lewis, 2009;Fischer et al, 2006;Gomez et al, 2006;Lutz et al, 2017;Wagner, Gais, Halder, Verieger, & Born, 2004) and the increased spreading activation theory (Cai et al, 2009;Monaghan et al, 2013).…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…Lateralising stimuli to the RH may highlight false memory effects, but naps rather than overnight sleep may also increase false memory effects (Chatburn et al, 2014). Indeed, the results of our study, and that of previous studies of lateralisation of DRM stimuli (Bellamy & Shillcock, 2007;Ito, 2001;Monaghan et al, 2017;Westerberg & Marsolek, 2003) are consistent with the possibility that false memories may be generated in the RH. Dominance of false memory generation in the RH would be consistent with the two principal theories for sleep-induced processing changes associated with false memories -the gist theory (Brainerd & Reyna, 2005;Durrant & Lewis, 2009;Fischer et al, 2006;Gomez et al, 2006;Lutz et al, 2017;Wagner, Gais, Halder, Verieger, & Born, 2004) and the increased spreading activation theory (Cai et al, 2009;Monaghan et al, 2013).…”
Section: Discussionsupporting
confidence: 89%
“…For the first objective of the sleep false memory behavioural effects, we found that unseen-lure words were more likely to be falsely recognised after a nap, than after a period of wake, consistent with the literature of sleep increasing false memories compared to an equivalent period of wake Monaghan et al, 2017;Pardilla-Delgado & Payne, 2017;Payne et al, 2009). The subsequent signal detection analyses demonstrated that the enhanced false memories were not only due to changes in response bias, but were effects of sleep on discriminability between unseen lure and unseen new words.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations